A drilling wellbore pressure calculation model considering the effect of gas dissolution and suspension - Zhang, Wenbo; Xue, Xianbo; Zhang, Chengcheng; Qu, Yue; Ke, Ke; Pan, Shaowei; Zeqin Li,; Zhang, Jianbo (Frontiers in Earth Science, 2022)
The complex formation pressure system and diverse formation fluid components during deepwater and deep drilling make it easy for gas intrusion accidents to occur. The dissolution and suspension of the intruded gas in the drilling fluid and the difference between the gas–liquid phase distribution characteristics and the gas–water two-phase flow characteristics in the wellbore lead to errors in the calculation of wellbore pressure and overflow assessment after gas intrusion. In this article, a wellbore multiphase flow model, considering gas dissolution and suspension is established, and the influence of gas dissolution and suspension in the drilling fluid on multiphase flow in the wellbore during overflow, well shutdown, and compression is analyzed with the model calculation results. The higher the drilling fluid density and yield stress are, the higher is the gas limit suspension concentration, when free gas is present in the wellbore. After the gas intrusion shutdown, when there are suspended and transported gases in the wellbore, the rate of pressure increase in the wellbore decreases after the shutdown, and the volume fraction of free gas decreases when the shutdown time is longer, and eventually all the gases will be suspended in the drilling fluid. During the pressure process, gas dissolution leads to an increase in the peak pressure in the wellbore and a delay in its occurrence; gas suspension leads to a decrease in the peak pressure in the wellbore and a delay in its occurrence. This article establishes a multiphase flow calculation model for the wellbore, considering both gas dissolution and suspension, which is a guideline for the calculation of wellbore pressure after gas intrusion.